Association of occupations with decreased semen quality in eastern China: a cross-sectional study of 12 301 semen donors. Issue 8 (26th August 2022) - Tang, Feng; Jiang, Zhaoqiang; Jin, Mingying; Sheng, Huiqiang; Feng, Lingfang; Chen, Junfei; Li, Yongxin; Huang, Jing; Xu, Ling; Lou, Jianlin
Abstract : Objectives: This study aims to examine the association between occupational factors and semen quality in semen donors in eastern China. Methods: We recruited 12 301 semen donors from 2006 to 2020 as the studying population. A self-designed questionnaire was applied for collecting lifestyle and work style information. Semen samples were analysed according to WHO guidelines. A crude and adjusted linear regression model was used to analyse the association between occupational factors and semen quality. Results: College students accounted for 36.2% of all semen donors. The majority (81.3%) of semen donors were between 18 year and 30 years. Soldiers or the police had the highest semen volume (the median value=3.8 mL), however, they had the lowest sperm concentration (53.6×10 6 /ml) and sperm motility (45.5%). Workers in finance or insurance had an elevated risk of low semen volume, sperm concentration and total sperm count ( OR =1.43, 1.57 and 1.98, respectively). Unemployed men had a high risk of low sperm concentration and low total sperm count ( OR =1.84 and 1.58, respectively). Working in the information technology industry had a deleterious effect on the progressive motility of sperm ( OR =1.27, 95% CI 1.03 to 1.57). Conclusion: Our study indicated that sedentary work style and intensive sports in certain professions might be associated with decreased semen quality. We reported evidence of becoming unemployed on the damage to semen quality. Hence, we advocate a healthy work style to improve semen quality in eastern China.